Transformasi Digital Sebagai Instrumen untuk Memperluas Aksesibilitas Layanan Publik - Yuli Santri Isma; Depita Kardiati; Muslem Muslem; Sarrah Kurnia Fadhillah; Jamiati KN; Fitria Akmal; Syarifah Chairunnisak (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study analyzes the role of digital transformation as a strategic instrument to expand public service accessibility in Indonesia. Through a Systematic Literature Review (SLR) of open-access national journals and relevant policy documents from the last decade, the research highlights how digitalization, particularly e-government implementation, enhances service efficiency, transparency, and inclusivity. Key findings indicate that digital platforms like SP4N-LAPOR! have improved public responsiveness and accountability, especially during the COVID-19 pandemic. However, challenges such as infrastructure disparities, uneven digital literacy, bureaucratic resistance, and data security risks hinder optimal outcomes. The study concludes that digital transformation significantly supports public service reform but requires integrated strategies, including infrastructure development, digital literacy programs, inclusive regulations, and multi-stakeholder coordination. These recommendations aim to bridge the digital divide and ensure equitable access to public services across all regions and vulnerable groups.